Tendência da prevalência de sobrepeso, obesidade, diabetes e hipertensão em mulheres brasileiras em idade reprodutiva, Vigitel 2008-2015 - Fernanda Gontijo Araújo (2018)
Introduction: Non Communicable Diseases (NCDs) and their risk factors, among women of childbearing age, beyond of been associated with increased cardiovascular risk, also imply a greater likelihood of adverse maternal and neonatal outcomes. International studies have shown high prevalences and increasing trends of NCDs and their risk factors in this specific population. Thus, the objective of this study was to analyze the temporal evolution of the prevalence of overweight, obesity, diabetes and hypertension in the population of Brazilian women of reproductive age between 2008 and 2015. Methods: This is a population-based time series study that used data from the Surveillance and Monitoring System for Risk Factors and Protection by Telephone Inquiry (Vigitel) of Brazilian women aged 18 to 49 years who answered the survey in the period from 2008 to 2015. The prevalence of overweight, obesity, diabetes and hypertension in each year was estimated for the study population, considering socio-demographic characteristics (age, schooling, home region, skin color and marital status). For the trends analysis, the Prais-Winsten generalized linear regression model and the annual percent change were used. Results: Prevalence of overweight and obesity in all age groups, schooling, color, marital status and region was observed to be increasing, except for the prevalence of overweight in women aged 30 to 39 years (p = 0.053), black (p = 0.558) and living in the southern region (p=0.075). The women studied had the highest increase (5.8%) in the prevalence of overweight compared to the Brazilian population (3.5%), and those from 18 to 29 years of age also had a greater increase (9.4%) in prevalence of this aggravation compared to 40 to 49 years (3.3%). Prevalence of diabetes (p = 0.087) and hypertension (p = 0.307) showed a steady trend. However, there was an increasing trend in the prevalence of diabetes among women aged 40-49 (p = 0.001), who lived without a partner (p = 0.023), 12 years or more (p = 0.007) and living in the North (p = 0.014) and Center-West (p = 0.018). Conclusion: Among the results found, it is worth noting the increasing and alarming prevalence of overweight and obesity, which are important risk factors for NCDs. In addition, there was a greater increase in the prevalence of overweight for younger women, which increases the likelihood of these to experience pregnancy complications associated with obesity, diabetes and hypertension.